Relational Delegation - Ricardo Alonso; Niko Matouschek (Institute for the Study of Labor (IZA), 2005)
We explore the optimal delegation of decision rights by a principal to a better informed but biased agent. In an infinitely repeated game a long lived principal faces a series of short lived agents. Every period they play a cheap talk game ala Crawford and Sobel (1982) with constant bias, quadratic loss functions and general distributions of the state of the world. We characterize the optimal delegation schemes for all discount rates and show that they resemble organizational arrangements that are commonly observed, including centralization and threshold delegation. For small biases threshold delegation is optimal for almost all distributions. Outsourcing can only be optimal if the principal is sufficiently impatient.
Keywords: D82; D23; L23; 330; delegation; cheap talk; relational contract; Kooperative Führung; Wiederholte Spiele; Agency Theory